Who killed Utopia? Cult conspiracy drama and a television imaginary. (January 2021) - Hill, Annette
This article focuses on the production and reception of television drama, specifically the case study of conspiracy thriller Utopia . The empirical research is based on 21 production interviews with the makers of the drama and 56 interviews with audience members and fans of the drama. The concept of the television imaginary is used as an analytical lens for investigating the various ways television itself, and audiences and fans, are imagined and implicated in the cancellation of a cult drama series. In particular, Barthes' early writing on a cultural imaginary is used to underscore the contrariness, the contra positions which creative producers, audiences and fans take, in the conspiracies and judgements surrounding the cancellation. Utopia conspiracies within and outside the television industry serve to legitimise and penalise the drama as a cult form; these conspiracies energise the subjective processes that shape an future imaginary for Utopia and drive its afterlife.